2022
DOI: 10.3390/nu14071531
|View full text |Cite
|
Sign up to set email alerts
|

Lansium domesticum—A Fruit with Multi-Benefits: Traditional Uses, Phytochemicals, Nutritional Value, and Bioactivities

Abstract: Lansium domesticum (Langsat, Meliaceae) is a tropical fruit mainly found in Southeast Asian countries, particularly in Thailand, Malaysia, Indonesia, and the Philippines. Traditionally, it is utilized as a folk treatment for eye inflammation, ulcers, diarrhea, dysentery, fever, spasms, flatulence, worms, insect bites, scorpion stings, and malaria. Additionally, it is utilized as a mosquito repellent, skin moisturizer and whitening agent. Pharmacological research showed that the plant has a wide array of bioact… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
16
0
3

Year Published

2022
2022
2025
2025

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 23 publications
(21 citation statements)
references
References 123 publications
(170 reference statements)
2
16
0
3
Order By: Relevance
“…In the underivatized fraction LH6-6, spathulenol, cadinol, and isoaromadendrene were detected; these compounds were previously detected in L. domesticum in fractions that are antifungal. 17,18 Likewise, in the underivatized LH7-6 fraction, cadinol was found and similarly detected in previous reports. 18 In our previous LC-MS/MS analysis, we reported that L. domesticum hexane fraction contained primarily of phenylpropanoids and polyketides (80.71%) and lipids and lipid-like molecules (18.78%).…”
Section: Network Pharmacology Of Predicted Compound-protein Interactionssupporting
confidence: 88%
See 1 more Smart Citation
“…In the underivatized fraction LH6-6, spathulenol, cadinol, and isoaromadendrene were detected; these compounds were previously detected in L. domesticum in fractions that are antifungal. 17,18 Likewise, in the underivatized LH7-6 fraction, cadinol was found and similarly detected in previous reports. 18 In our previous LC-MS/MS analysis, we reported that L. domesticum hexane fraction contained primarily of phenylpropanoids and polyketides (80.71%) and lipids and lipid-like molecules (18.78%).…”
Section: Network Pharmacology Of Predicted Compound-protein Interactionssupporting
confidence: 88%
“…On the other hand, the derivatized fractions yielded fatty acids, monoglycerides, and some sterols. In the underivatized fraction LH6‐6, spathulenol, cadinol, and isoaromadendrene were detected; these compounds were previously detected in L. domesticum in fractions that are antifungal 17,18 . Likewise, in the underivatized LH7‐6 fraction, cadinol was found and similarly detected in previous reports 18 .…”
Section: Resultssupporting
confidence: 64%
“…Famili ini memiliki sekitar 600 spesies dan 53 genus yang tersebar luas di daerah tropis maupun subtropis [1] . Lansium domesticum yang dikenal sebagai langsat adalah tumbuhan tropis yang banyak ditemukan di Asia Tenggara, khususnya di Thailand, Malaysia, Indonesia, dan Filipina [2] .…”
Section: Pendahuluanunclassified
“…It was also reported that more than 80% of people worldwide rely on traditional medicines as a primary source of healthcare, involving the utilization of plant extracts or their phytoconstituents [4]. Recently, plantderived metabolites have become greatly important due to their structural diversity and promising bioactivities [5][6][7]. utilized for bruises, bronchitis, and hepatitis [16].…”
Section: Introductionmentioning
confidence: 99%